The impact of unemployment and inflation on economic growth in Nigeria (1981-2014) - Abdulsalam S. Ademola; Abdullahi Badiru (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2016)
Purpose - To investigate and determine the effects of unemployment and inflation on economic performance in Nigeria within the specified period as in the title and to establish the relationship between unemployment and inflation with Real Gross Domestic Product in Nigeria. Design/methodology/approach - Ordinary Least Square (OLS) technique was adopted with various diagnostic test to determine how fit are the data for the analysis. Findings - The result of Diagnostic test indicates that data for the analysis are stationary at level and there are 2 cointegrating equation implying that there exist long-run relationship between RGDP, Unemployment and inflation. The results indicated that unemployment and inflation are positively related to economic growth. Research limitations/implications - The study uses only OLS and Diagnostic to carried out the analysis and it only cover the period from 1981 to 2014. Originality/value - The originality of this study lies on findings and interpretation of the result of regression analysis. The positive relationship between unemployment, inflation and RGDP indicates that Nigeria RGDP is driven by oil revenue that employs very limited highly skilled labour and the price of output of crude oil is determined externally which may not response as expected to growth of output in the country.
Keywords: E11; 330; cointegration; economic growth; inflation and unemployment